Comparative Genome-Centric Analysis of Freshwater and Marine ANAMMOX Cultures Suggests Functional Redundancy in Nitrogen Removal Processes - Ali, Muhammad; Shaw, Dario Rangel; Albertsen, Mads; Saikaly, Pascal E. (Frontiers in Microbiology, 2020)
Two physiologically distant anammox populations have been identified, one predominantly detected in freshwater (non-saline) and another in marine (saline) ecosystems. However, there is a lack of understanding of the interaction between anammox bacteria and the flanking microbial communities in both ecosystems. Here, we present a comparative genome-based exploration of two different anammox bioreactors, through the analysis of 23 metagenome-assembled genomes (MAGs), twelve from freshwater anammox reactor (FWR) and eleven from marine anammox reactor (MWR). Some of these MAGs are recovered using 3rd generation long-read sequencing (Oxford Nanopore) technology corrected with the 2nd generation short-read sequencing data. To understand the contribution of individual microbiome members to community functions, we applied an algorithm, index of replication (iRep), to determine which bacteria are actively replicating. Using genomic content and iRep information, we provided a potential ecological role for the dominant members of the community based on the reactor operating conditions. In the non-saline system, anammox (Candidatus Brocadia sinica) and auxotrophic neighboring bacteria belonging to the phyla Ignavibacteriae and Chloroflexi might interact to reduce nitrate to nitrite for direct use by anammox bacteria. Whereas, in the saline reactor, anammox bacterium (Ca. Scalindua erythraensis) and flanking community belonging to phyla Planctomycetes (different than anammox bacteria) – which persistently growing in the system – may catabolize detritus and extracellular material and recycle nitrate to nitrite for direct use by anammox bacteria. Despite different microbial communities, there was functional redundancy in both ecosystems. These results signify the potential application of marine anammox bacteria for treating saline N-rich wastewaters.